Chemical Enhancer Solubility in Human Stratum Corneum Lipids and Enhancer Mechanism of Action on Stratum Corneum Lipid Domain - Ibrahim, Sarah A. (2009)
Previously, chemical enhancer-induced permeation enhancement on human stratum corneum (SC) lipoidal pathway at enhancer thermodynamic activities approaching unity in the absence of cosolvents (defined as Emax) was determined and hypothesized to be related to the enhancer solubilities in the SC lipid domain. The objectives of the present study were to (a) quantify enhancer uptake into SC lipid domain at saturation, (b) elucidate enhancer mechanism(s) of action, and (c) study the SC lipid phase behavior at Emax. It was concluded that direct quantification of enhancer uptake into SC lipid domain using intact SC was complicated. Therefore a liposomal model of extracted human SC lipids was used. In the liposome study, enhancer uptake into extracted human SC lipid liposomes (EHSCLL) was shown to correlate with Emax. Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and differential scanning calorimetry (DSC) were used to evaluate lipid phase alterations in enhancer-treated intact SC. IR spectra demonstrated an increase in the lipid domain fluidity and DSC thermograms indicated a decrease in the phase transition temperature with increasing Emax. These results suggest that the enhancer mechanism of action is through enhancer intercalation into SC intercellular lipids and subsequent lipid lamellae fluidization related to enhancer lipid concentration.